2014
DOI: 10.1128/mcb.01532-13
|View full text |Cite
|
Sign up to set email alerts
|

LIN-35/Rb Causes Starvation-Induced Germ Cell Apoptosis via CED-9/Bcl2 Downregulation in Caenorhabditis elegans

Abstract: Apoptosis is an important mechanism for maintaining germ line health. In Caenorhabditis elegans, germ cell apoptosis occurs under normal conditions to sustain gonad homeostasis and oocyte quality. Under stress, germ cell apoptosis can be triggered via different pathways, including the following: (i) the CEP-1/p53 pathway, which induces germ cell apoptosis when animals are exposed to DNA damage; (ii) the mitogen-activated protein kinase kinase (MAPKK) pathway, which triggers germ cell apoptosis when animals are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 70 publications
3
18
0
Order By: Relevance
“…Stress-induced repression of translation is widely accepted to be connected to the formation of stress granules (Lascarez-Lagunas et al, 2014; Mollet et al, 2008), and we found this to be true as well for P54a and P54b heat-induced granules in zebrafish embryos. In our experiments, P54 heat-induced granules and TIAL-1-labeled stress granules showed the same responses to the blockade of translation by cycloheximide or by puromycin.…”
Section: Discussionsupporting
confidence: 74%
“…Stress-induced repression of translation is widely accepted to be connected to the formation of stress granules (Lascarez-Lagunas et al, 2014; Mollet et al, 2008), and we found this to be true as well for P54a and P54b heat-induced granules in zebrafish embryos. In our experiments, P54 heat-induced granules and TIAL-1-labeled stress granules showed the same responses to the blockade of translation by cycloheximide or by puromycin.…”
Section: Discussionsupporting
confidence: 74%
“…Heat shock and oxidative stress induce germ cell apoptosis through the MAPK pathway and independently of EGL-1 [ 42 ]. Germ cell apoptosis induced by starvation is regulated by CED-9/BCL-2 down-regulation via LIN-35/RB [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, quiescence might substitute for the repressive effects of FBF-1 and FBF-2 by repressing translation on a global level. Global repression of translation is a conserved stress response ( Spriggs et al, 2010 ), and the stress of starvation represses translation of at least a few genes in C. elegans ( Lascarez-Lagunas et al, 2014 ). Another possibility is that stem cell maintenance might be regulated by a metabolite or metabolic process whose levels change during quiescence.…”
Section: Discussionmentioning
confidence: 99%